The status of the genus Hokkaidocephala Tenora, Gulyaev & Kamiya, 1999 (Cestoda: Anoplocephalidae), parasites of the endemic Japanese field mice (Apodemus spp.) - Haukisalmi, Voitto; Asakawa, Mitsuhiko; Gubányi, András (Zootaxa, 2008)
The present study reconsiders the status of the genus Hokkaidocephala Tenora, Gulyaev & Kamiya, 1999 by examining available specimens of the type species H. apodemi (Iwaki, Tenora, Abe, Oku & Kamiya, 1994) (syn. Andrya apodemi) and comparing them with related anoplocephaline cestodes. It is shown that Hokkaidocephala apodemi does not differ fundamentally from related genera in the development of the reproductive organs, contrary to the argument of Tenora et al. (1999). In Hokkaidocephala and related genera (Anoplocephaloides Baer, 1923 s. str. and Microcephaloides Haukisalmi, Hardman, Hardman, Rausch & Henttonen, 2008), sperm appears in the seminal receptacle (female organ) simultaneously or slightly earlier than in the seminal vesicles (male organs) and the ovary and vitellarium are absent in postmature proglottides where testes still persist and usually reach their maximum size. However, Hokkaidocephala is considered here a valid genus differentiated from the related genera by its unique uterine structure and development. Presently, Hokkaidocephala includes two host-specific species [H. apodemi and H. baeri (Rausch, 1976) n. comb. (= Anoplocephaloides baeri Rausch, 1976)] parasitizing endemic Japanese field mice (primarily Apodemus argenteus).